Optimized drying parameters of water hyacinths (Eichhornia crassipes. L) - Casas, Edgardo V. (Science Diliman, 2012)
The study investigated the optimum drying conditions of water hyacinth to contribute in the improvement of present drying processes. The effects of independent parameters (drying temperature, airflow rate, and number of passes) on the responses were determined using the Response Surface Methodology. The response parameters were composed of (1) final moisture content, (2) moisture ratio, (3) drying rate, (4) tensile strength, and (5) browning index. Box and Behnken experimental design represented the design of experiments that resulted in 15 drying runs. Statistical analysis evaluated the treatment effects. Drying temperature significantly affected the drying rate, moisture ratio, and browning index. Airflow rate had a significant effect only on the drying rate, while the number of passes significantly affected both the drying rate and browning index. The optimized conditions for drying the water hyacinth were at drying temperature of 90C, airflow rate of 0.044m3/s, and number of passes equivalent to five. The best model that characterizes the drying of water hyacinth is a rational function expressed as: .... [ABSTRACT FROM AUTHOR]